Endophthalmitis following intravitreal triamcinolone acetonid injection – a case report - Jamrozy-Witkowska, Agnieszka; Grabska-Liberek, Iwona; Kowalska, Katarzyna; Oficjalska-Młyńczak, Jolanta (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: to report a case of acute endophthalmitis following intravitreal triamcinolone acetonide injection. Material and methods: a 54-year-old woman with diabetic macular edema developed endophthalmitis after triamcinolone injection. First she was treated with intravitreal antibiotic injections and next with four surgeries – facovitrectomy, revitrectomy, silicone oil removal and revitrectomy. Results: the initial visual acuity was 0.5. From the vitreous cultured Staphylococcus epidermidis. Depite the intensive medical intervention, the toxic retinal damage occurred and the final visual acuity was hand movement. Conclusions: intravitreal triamcinolone injections can induce bacterial endophthalmitis, which has a devastating effect on the ocular tissues and results in severe loss of vision. The procedure of injection in diabetic and immunocompromised patients should be performed with great care.